As representações sociais de ciência: um estudo a partir de um curso de licenciatura em ciências biológicas - Souza, Tamires Cristina de (Universidade Federal de São Carlos, 2020)
This is a qualitative research aiming to investigate Science social representations of Biology’s undergraduate students and the possible relationships with their process of initial teacher training, focusing on the question: What are the social representations that Biology undergraduate students from a Public University have about Science, and what are the possible impacts/contributions of the initial teacher training on the development of these representations? The participants of this research were 89 students enrolled on a Biology course from a Public University. The research had two main steps: the first one with the collection and organization of the possible elements from the Science social representations central nucleus and the peripheric system on the students; and the second one with the search for evidences of the possible impacts/contributions of the initial teacher training on the students representations construction. The methodology applied here is based on the main method and technic of the social representations’ central nucleus research: “Free Association of Words” technique. In addition, the research’s second step used complementary interviews, from which two categories emerged: 1) LCB/ course subjects and 2) events/extracurricular activities. The data obtained with the “Free Association of Words” technique was analyzed with a prototypical analysis, and the data from the interviews was analyzed considering Bardin’s (1977) content analysis. Comparing the representations of students from the beginning and ending of the course, there was a great similarity between the elements that form the possible central nucleus of these groups. In this region there was the sharing of the elements knowledge, study and experiment. Most of the differences were found in the peripheral region, which reveals the presence of elements of a tentative character (search and curiosity) and social (domination) only for the group of ending students. In this way, the data resulting from the research leads us to verify that the reflections promoted by the course subjects and the experiences made possible by the extracurricular activities have contributed to the formation of a broader sense of Science as a human construction.
The social representations of science: a study from a degree course in biological sciences
Keywords: Representação social; Ciência; Formação inicial; Social representation; Science; Initial teacher training; CIENCIAS HUMANAS::EDUCACAO